2017
DOI: 10.1021/acs.analchem.7b01175
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Switching Strategy for Promoting Fluorescent Sensing of Biologically Relevant Species: A Simple Near-Infrared Cyanine Dye Highly Sensitive and Selective for ATP

Abstract: We report a strategy for enhanced performance of fluorescent sensing of biologically relevant species that often bind with natural receptors via multiple interactions. We propose making a fluorescent sensory molecule to form H-aggregates such that its emission is quenched leaving a low background, and upon binding to a biologically relevant species, the aggregate switches to another form in which the fluorescent species is better protected to afford a stronger emission signal. Meanwhile, the aggregated fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Considering the advancement of nanotechnology and nanoscience, nanostructured micellar probes have been considered as a promising candidate for bio-sensing owing to their structural flexibility and versatility [62]. However, only a handful of luminescent biosensor probes based on micellar systems appeared in the recent literature [16][17][18][19][20][63][64][65][66][67][68][69][70][71][72][73][74]. We will provide a very brief glimpse on these luminescent biosensors, which are used to create self-assembled nanostructure materials showing promise for use as next generation potential as "functional materials".…”
Section: Luminescent Micellar Systems For Bio Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the advancement of nanotechnology and nanoscience, nanostructured micellar probes have been considered as a promising candidate for bio-sensing owing to their structural flexibility and versatility [62]. However, only a handful of luminescent biosensor probes based on micellar systems appeared in the recent literature [16][17][18][19][20][63][64][65][66][67][68][69][70][71][72][73][74]. We will provide a very brief glimpse on these luminescent biosensors, which are used to create self-assembled nanostructure materials showing promise for use as next generation potential as "functional materials".…”
Section: Luminescent Micellar Systems For Bio Sensingmentioning
confidence: 99%
“…Likewise, Jiang et al recently reported a luminescent micellar system [20] for ATP, comprised of a cationic surfactant, dodecyltrimethylammonium bromide (DTAB), and a near infrared (NIR) emissive cyanine dye. As mentioned above, a similar π−π staking within ATP and dye molecule triggered an effective energy transfer (ET) from the dye to ATP that resulted in significant quenching of emission intensity.…”
Section: Luminescent Micellar Systems For Bio Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The affinity of these CyD hosts for nucleotides or nucleosides has been well investigated, although there are still few applications of CyDs to chemical sensors [ 19 , 20 , 21 , 22 , 23 , 24 ]. On the other hand, ATP recognition has been studied because of its significant roles in biological systems, and thus a number of ATP-targeting fluorescent probes have been reported over the last few decades [ 25 , 26 , 27 ]. However, there have been few examples of turn-on type chemical indicators that can distinguish nucleoside triphosphate from similar derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, the ATP concentration in the human body is strictly self-regulated. However, intensive research evidences have also confirmed that abnormal ATP concentration is closely indicative to several diseases, for instance, hypoglycemia, cardiovascular disease, Alzheimer's disease, as well as various cancers [5][6][7]. In nerve system, ATP connects non-neural cells and nerve cells to perform the important function of sensory transmission, therefore monitoring trace amounts of ATP is conducive to understand its integration in the brain [8].…”
Section: Introductionmentioning
confidence: 99%